SARS-CoV-2 transmission among healthcare workers and related potential stigma during COVID-19 pandemic - Solikhah Solikhah; Ratu Matahari; Dwi Sarwani Sri Rejeki; Fitri Arofiati; Farah Nurul Yanis Syarifa (Intelektual Pustaka Media Utama, 2023)
A limited number of studies are available on COVID-19 patients by disease cluster. We aimed to evaluate the healthcare cluster and stigmatization during the COVID-19 outbreak in Batam, Indonesia. A qualitative study using an empirical phenomenological approach and in-depth interviews with content and thematic analysis was conducted. The informants admitted that they were infected with the severe acute respiratory syndrome coronavirus 2 (SAR-CoV-2) virus due to non-compliance to COVID-19 protocols, such as removing masks and talking face to face during breaks in meetings held in poor-ventilated rooms. A social stigma was experienced by these healthcare workers because people tended to keep their distance and ostracized them because they were afraid of COVID-19. Healthcare workers tend to be stigmatized and ostracized by the community. A clinical guideline and public health policy should be established by involving community leaders to minimize the psychological pressure experienced by healthcare workers. The results of this study can help policy makers to improve risk management standards in controlling the spread of the SARS-CoV-2 virus in health center to create publich health trust in eliminating COVID-19.